Effectiveness of Different Hormonal Treatment Protocols on Treatment of Postpartum Anoestrus in Cross-Bred Dairy Cows - Rana, P.K.; Gautam, G.; Devkota, B.; Shah, S.K.; Barsila, S.; Kadariya, I.P. (Nepalese Veterinary Journal, 2018)
Postpartum anoestrus (PPA) is one of the major factors causing prolonged calving interval & that leading to decreased annual milk production. Hormonal treatments can be effective tools for treatment of PPA when nutritional & environmental management are good. So, objective of this study was to know the comparative effectiveness of different hormonal protocols on treatment of PPA in cross-bred dairy cows. Used protocols were: single dose of GnRH, Ovsynch with TRIU-B and single dose of PGF2α injection which were used in three different groups, each containing ten animals. GnRH and Ovsynch with TRIU-B were used in postpartum true anoestrus cattle with inactive ovaries while PGF2α was used in postpartum silent oestrus condition having palpable corpus luteum and the condition were identifi ed through rectal palpation and history record. Cows treated with Ovsynch+TRIU-B showed higher oestrus expression rate within one week (80%) than cows treated with GnRH (10%) and PGF2α (50%). Ovulation rate was also comparatively higher in Ovsynch+TRIU-B group (100%) than GnRH (90%) and PGF2α (70%). But the pregnancy rate, checked after 45 days of first AI through rectal palpation, was comparatively higher in GnRH group (40%) than in Ovsynch+TRIU-B (30%) and PGF2α (20%). Among treated cows, pregnancy rate was found to be signifi cantly higher (P=0.02) in cows with ≥100 days duration of postpartum anoestrus (53.84%) than in cows with 100 days duration (0%). In conclusion, ovsynch with intravaginal progesterone (p4) releasing device was more effective at inducing oestrus and synchronizing ovulation than the single GnRH injection. However, single GnRH injection was as effective as ovsynch with intravaginal p4 releasing device for pregnancy outcomes in anoestrous crossbred dairy cows in a commercial dairy farm where formulated concentrate ration is daily fed.